FREQUENCY DISCRIMINATOR FOR AIRCRAFT RADIONAVIGATION DOPPLER SYSTEM BASED ON MICROCONTROLLER - I.V. Aksenov (Penza State University Publishing House, 2021)
Background. The object of the study is an aircraft radio navigation system. The subject of this research is the methodology for constructing an airborne radio navigation system based on the Doppler effect. The aim of the work is to develop a digital frequency discriminator, which is the main unit in the method of applying the Doppler effect in the construction of a speed and drift meter. Materials and methods. A technique based on the Doppler effect was used to describe the process of determining the speed of an aircraft and its drift angle. The concepts of digital frequency discriminator are introduced. Results. The proposed approach shows the development process of a four-beam dual-frequency DSS with double frequency conversion, including a digital frequency discriminator based on the MC. Conclusion. This implementation is especially relevant for unmanned aerial vehicles, since it has a high measurement and calculation accuracy, low power consumption, and fault tolerance.